ANALISIS KETERAMPILAN SHOOTING MENGGUNAKAN KAKI BAGIAN DALAM PADA PERMAINAN SEPAK BOLA BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN JASMANI UNIMUDA SORONG - Sugiono Sugiono; Waskito Aji Suryo Putro; Istiyono (CV. ADIBA AISHA AMIRA, 2024)
The aim of this study was to analyze the skill of shooting using the inside of the foot in football among Physical Education students at Unimuda Sorong. The research adopted a quantitative descriptive approach. The method used was a survey method employing a shooting test instrument for data collection. The research subjects comprised 16 third-semester physical education students. The analysis technique applied was descriptive statistics, presenting frequencies in percentage form. According to the research analysis, the skill of shooting using the inside of the foot in soccer among Physical Education students at Unimuda Sorong is categorized as follows: excellent, 0 individuals or 0%; good, 5 individuals or 31.25%; adequate, 6 individuals or 37.5%; inadequate, 3 individuals or 18.75%; and very inadequate, 2 individuals or 12.5%. The majority fell into the 'adequate' category, encompassing 6 individuals or 37.5%.